Association of daily physical activity and sedentary behaviour with protein intake patterns in older adults - Lourida, Ilianna (2021)
Funding Information: This research work is part of the EU-funded project PROMISS (?PRevention Of Malnutrition In Senior Subjects in the EU?) within the framework of Horizon 2020 research and innovation programme, contract No.678732. The Newcastle 85+ Study has been funded by the Medical Research Council, Biotechnology and Biological Sciences Research Council and the Dunhill Medical Trust. The research was also supported by the National Institute for Health Research (NIHR) Newcastle Biomedical Research Centre, based at Newcastle upon Tyne Hospitals NHS Foundation Trust and Newcastle University. LiLACS NZ data collection was supported by a programme and project grant from the New Zealand Health Research Council (09-069, 10-599), and a grant from the New Zealand Ministry of Health. Manuscript review was supported by the Joyce Cook Chair in Ageing Well foundation grant (NK) and the AWESSoM National Science Challenge programme (RT, AR) from NZ. The Dutch National Food Consumption Survey in older adults was funded by the Dutch Ministry of Health, Welfare and Sports. The Finnish National FINDIET surveys has been funded by the Finnish Institute for Health and Welfare (THL) (former National Public Health Institute KTL). The INRAN-SCAI 2005?06 survey was funded by the Italian Ministry of Agriculture, project ?Qualita? alimentare?. Acknowledgments: Newcastle 85+ Study acknowledges the operational support of the North of England Commissioning Support Unit (formerly NHS North of Tyne) and of the local general prac-titioners and their staff. We also thank the research nurses, dietary coders, management and clerical team for outstanding work throughout, as well as many colleagues for their expert advice. Thanks are due especially to the study participants and, where appropriate, their families and carers. LiLACS NZ acknowledges the expertise of the Western Bay of Plenty Primary Health Organisation, Ng? Mat?puna Oranga Kaupapa M?ori Primary Health Organisation, Te Korowai Aroha Trust, Te R?nanga o Ng?ti Pikiao, Rotorua Area Primary Health Services, Ng?ti Awa Research & Archives Trust, Te R?nanga o Ng?ti Irapuaia, and Te Wh?nau-?-Apanui Community Health Centre in conducting the study through the Bay of Plenty and Rotorua areas. We thank all participants and their wh?nau for participation, and the local organisations that promoted the study. LiLACS NZ thanks the Ropu Kaitiaki: Hone and Florence Kameta, Betty McPherson, Paea Smith, Leiana Reynolds, and Waiora Port for their guidance. We wish to thank the participants in the Dutch National Food Consumption Survey older adults, the municipalities that extracted random samples of individuals from their population registers. Our special thanks go to all the interviewers for conducting the fieldwork. We would also like to extend our thanks to the staff of the International Agency for Research on Cancer (IARCfor providing us with EPIC-Soft updates for the dietary assessment, GfK Panel Services for their expertise on the fieldwork and the expert committee for their comments on proposals. Finally, we wish to acknowledge the help provided by our current and former colleagues from RIVM on the design, preparation, fieldwork, and/or data handling. FINDIET survey wants to acknowledge all the survey participants and the nutritionists conducting the field work. We also wish to thank our colleagues in THL who participated in the planning, preparation, fieldwork, data handling, software development or food composition database administration in FINDIET survey as well as in FINRISK study. Funding Information: Funding: This research work is part of the EU-funded project PROMISS (“PRevention Of Malnutrition In Senior Subjects in the EU”) within the framework of Horizon 2020 research and innovation programme, contract No.678732. The Newcastle 85+ Study has been funded by the Medical Research Council, Biotechnology and Biological Sciences Research Council and the Dunhill Medical Trust. The research was also supported by the National Institute for Health Research (NIHR) Newcastle Biomedical Research Centre, based at Newcastle upon Tyne Hospitals NHS Foundation Trust and Newcastle University. LiLACS NZ data collection was supported by a programme and project grant from the New Zealand Health Research Council (09-069, 10-599), and a grant from the New Zealand Ministry of Health. Manuscript review was supported by the Joyce Cook Chair in Ageing Well foundation grant (NK) and the AWESSoM National Science Challenge programme (RT, AR) from NZ. The Dutch National Food Consumption Survey in older adults was funded by the Dutch Ministry of Health, Welfare and Sports. The Finnish National FINDIET surveys has been funded by the Finnish Institute for Health and Welfare (THL) (former National Public Health Institute KTL). The INRAN-SCAI 2005–06 survey was funded by the Italian Ministry of Agriculture, project ‘Qualita’ alimentare’. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.